Economic development - Todaro, Michael P.; Smith, Stephen C. (Boston : Pearson Addison Wesley, 2012)
"Economic Development presents theory in the context of policy debates, so you see how theory and applied studies relate to the problems and prospects of developing countries. In the Tenth Edition, the authors integrate new discussions of recent thinking in areas such as environmental resources, gender, governance, inequality and poverty, and microfinance."--BOOK JACKET.
Includes bibliographical references and indexes.
Keywords: Economic development